All‐Optical Active Q‐Switching: An All‐Optical, Actively Q‐Switched Fiber Laser by an Antimonene‐Based Optical Modulator (Laser Photonics Rev. 13(4)/2019). Issue 4 (8th April 2019) - Wang, Yunzheng; Huang, Weichun; Wang, Cong; Guo, Jia; Zhang, Feng; Song, Yufeng; Ge, Yanqi; Wu, Leiming; Liu, Jie; Li, Jianqing; Zhang, Han
Abstract : In article number1800313, Han Zhang and co‐workers demonstrate an all‐optical, actively Q ‐switched fiber laser enabled by an antimonene‐based all‐optical modulator. The pulsed pump light is absorbed by the 2D antimonene and induces intensity modulation of the signal light, causing the regulation of the intra‐cavity quality factor and the generation of Q ‐switching pulses.